2012
DOI: 10.1097/acm.0b013e31823aba03
|View full text |Cite
|
Sign up to set email alerts
|

Thinking About Giving Up Clinical Practice? A Gender-Stratified Approach to Understanding Junior Doctorsʼ Choices

Abstract: Workplace factors predict the wish for leaving clinical care for junior doctors. Male and female junior doctors seem to have different priorities in the workplace, which should be addressed in order to retain them in patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 33 publications
2
47
1
Order By: Relevance
“…The process of losing physicians from public teaching hospitals typically begins after graduation. Among the publications studied [42, 43, 4547, 4951], there is no unanimity with regard to the factors that affect turnover, with aspects such as age, specialty, and post-graduation studies having been identified. However, there is a trend to agree that the more specialized physicians tend to remain in higher-complexity services.…”
Section: Discussionmentioning
confidence: 99%
“…The process of losing physicians from public teaching hospitals typically begins after graduation. Among the publications studied [42, 43, 4547, 4951], there is no unanimity with regard to the factors that affect turnover, with aspects such as age, specialty, and post-graduation studies having been identified. However, there is a trend to agree that the more specialized physicians tend to remain in higher-complexity services.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies investigating intention to leave use single-item measures, such as thinking about giving up clinical practice [2] or intention to change profession [14]. To our knowledge, no validation study comparing single-item measures and multiple-item measures of intention to leave has yet been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…USA [1], Germany [2], Finland [3], Australia [4] and OECD Countries [5]). Although the volume of admissions to medical schools is adequate in most countries to overcome this shortage, not all medical students begin working or spend the duration of their working life in direct patient care [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations